Modeling and simulation for microelectronic packaging assembly : manufacturing, reliability, and testing - Liu, S. (Sheng), 1963-; Liu, Yong, 1962- ([Beijing] : Chemical Industry Press, 2011)
'This book is primarily concerned with studies of electronic packaging in assembly manufacture processes and failure mechanisms in assembly manufacture processes and tests through modeling and simulation'--
Includes bibliographical references and index.
Keywords: Microelectronic packaging -- Simulation methods